Sistem Informasi Geografis Pemetaan Tempat Kos-Kosan Berbasis Web Di Kota Padang - Trianto, Muhammad Wawan Fakhry; Sularno, Sularno; Zulfahmi, Zulfahmi (Jurnal Sistem Informasi Dan Informatika, 2023)
Geographic Information System is a geospatial software system that has the ability to build, store, manage and display geographically referenced information. This research is motivated by the availability of very limited information regarding the location of boarding houses which causes students, especially new students, who tend not to have accurate and relevant information so they do not know which locations have affordable boarding houses, near lectures, workplaces, or educational institutions. Therefore the purpose of this research is to provide complete information about boarding houses, students do not need to spend time visiting boarding houses one by one in search of information about boarding houses. With an informative web-based geographic information system mapping boarding houses and interesting so that it can make it easier for users, especially new students who want to do a search for boarding houses around the Padang area. The results of this Web-based Boarding Map Mapping Information System research can provide information about boarding houses which can make it easier for users to search. Ari boarding houses such as facilities, room availability, rental fee information, and the location of the boarding house, and a map to show the location of the boarding house.